2019
DOI: 10.20944/preprints201908.0020.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Meteorological and Agricultural Drought Indicators across Ethiopia

Abstract: 19Meteorological drought indicators are commonly used for agricultural drought contingency planning in 20Ethiopia. Agricultural droughts arise due to soil moisture deficits. While these deficits may be caused by 21 meteorological droughts, the timing and duration of agricultural droughts need not coincide with the 22 onset of meteorological droughts due to soil moisture buffering. Similarly, agricultural droughts can 23 persist even after the cessation of meteorological droughts due to delayed hydrologic proce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Its reliability is also likely to be higher in warm climates (such as Ethiopia) 2 where the hydrology is not affected by spring snowmelt. PDSI has also been used widely to characterize 3 agricultural droughts [13,43,44]. Studies have shown that PDSI correlates strongly with SPI values 4 computed using higher accumulations [45,46].…”
mentioning
confidence: 99%
“…Its reliability is also likely to be higher in warm climates (such as Ethiopia) 2 where the hydrology is not affected by spring snowmelt. PDSI has also been used widely to characterize 3 agricultural droughts [13,43,44]. Studies have shown that PDSI correlates strongly with SPI values 4 computed using higher accumulations [45,46].…”
mentioning
confidence: 99%